Default Prediction in Pakistan using Financial Ratios and Sector Level Variables - Suresh Ramakrishnan; Agha Amad Nabi; Melati Ahmad Anuar (International Journal of Economics and Financial Issues, 2016)
Default prediction provides a way to control and direct firms in achieving their goals. The common approach in this regard has been to study the relationship between set of explanatory variables and financial distress. The study served specific objectives by highlighting the sectors impact on financial behavior of Pakistani listed firms across sectors. The study looks into the sector specific attributes that affect the bankruptcy prediction determinants. Since sectors operate in business environments which are subject to different levels of growth, competiveness and market concentration. The study will investigate the relationship of several independent firm-level, sector level variables that have to be examined with dependent variable. Financial variables nature is not normal so logit used for the nature and also financial distress is binomial variable. In addition, the Company may provide the possibility of financial distress and indicates an argument that this study used independent variables that are best predictors of financial distress.